Information Sharing in Managing Collaborative Relationships: an Analytical and Empirical Investigation - Andotra, Neetu; Chalotra, Vipul (Indian Journal of Marketing, 2011)
Information sharing embedded in collaborative relationships in the supply chain improves operational efficiency by reducing logistics costs, augmenting financial structure&functioning, reduction in behaviour uncertainty, leading to overall competitive strength. The paper empirically and analytically investigates information sharing behaviour among 44 managers of small manufacturing firms, 74 wholesalers and 120 retailers in the district Udhampur of J&K State. The data, after purification&validation through factor analysis, was subjected to multivariate tools. The results of t test, Chi-square and hierarchal regression model revealed a significant mean difference between wholesalers and retailers on the dimensions of information sharing, positive association between information sharing and operational efficiency and trust&willingness as the predictors of information sharing in collaborative relationships. The study emphasized on bringing attitudinal changes among partners through education&collaborative activities, creation of a hub for information dissemination and technology support of the Government.